Knockdown of hsa_circ_0059955 Induces Apoptosis and Cell Cycle Arrest in Nucleus Pulposus Cells via Inhibiting Itchy E3 Ubiquitin Protein Ligase - Kong D; Gu R; Zhang C; Yin R (Dove Medical Press, 2020)
Daliang Kong, Rui Gu, Chengtao Zhang, Ruofeng Yin Department of Orthopedics, China-Japan Union Hospital, Changchun, Jilin 130031, People’s Republic of ChinaCorrespondence: Ruofeng YinDepartment of Orthopedics, China-Japan Union Hospital, Changchun, Jilin 130031, People’s Republic of ChinaEmail yrf_wind@jlu.edu.cnBackground: Circular RNAs (circRNAs) play an important role in the progression of intervertebral disc (IVD) degeneration (IVDD). Using bioinformatics analysis, we have found that the expression of circRNA hsa_circ_0059955 was significantly downregulated in IVDD tissues. However, the relevant mechanism of hsa_circ_0059955 in the progression of IVDD remains unclear.Methods: CCK-8 and flow cytometry assays were used to evaluate cell proliferation and apoptosis. In addition, Western blot assay was used to detect the expressions of ITCH, p73, CDK2 in nucleus pulposus (NP) cells. Moreover, a puncture-induced IVDD rat model was established to explore the role of hsa_circ_0059955 in IVDD.Results: The level of hsa_circ_0059955 was significantly decreased in IVDD tissues from IVDD patients. Itchy E3 ubiquitin protein ligase (ITCH) is the host gene of hsa_circ_0059955, and downregulation of hsa_circ_0059955 significantly decreased the expression of ITCH in NP cells. In addition, downregulation of hsa_circ_0059955 markedly inhibited proliferation and induced apoptosis and cell cycle arrest in NP cells. Moreover, in vivo study illustrated that overexpression of hsa_circ_0059955 ameliorated IVDD in rats.Conclusion: Downregulation of hsa_circ_0059955 could induce apoptosis and cell cycle arrest in NP cells in vitro, while overexpression of hsa_circ_0059955 attenuated the IVDD in a puncture-induced rat model in vivo. Therefore, hsa_circ_0059955 might serve as a therapeutic target for the treatment of IVDD.Keywords: intervertebral disc degeneration, hsa_circ_0059955, Itchy E3 ubiquitin protein ligase, p73